ANALISIS KUALITAS LAYANAN JARINGAN INTERNET WIFI.ID MENGGUNAKAN PARAMETER QOS (Quality Of Service) - Westi Yulia Pusvita; Yasdinul Huda (Universitas Negeri Padang, 2019)
This research originated from the quality of the wifi.id internet network in the area of Air Tawar which is varied and more suitable for locations that are farther away than the access points. This study aims to find the quality of the wifi.id internet network in the Air Tawar area, and to obtain the results of delay, packet loss, and throughput generated in measuring the quality of the wifi.id network and compare it with the TIPHON standard. This research is a descriptive research. The population of this study is the wifi.id access point in the Air Tawar area with a research sample of three wifi.id access point locations on Air Tawar. This research was conducted by measuring the quality of wifi.id using the axence nettols 5 application for 10 days in the morning, afternoon and evening. From the results of the research after analysis obtained: (1) The best delay measurement is on Jl. Gajah TP 1 with a value of 8.5 ms and the worst on Jl. Parkit TP 4 with a value of 64.8 ms. (2) The best packet loss measurement is on Jl. Gajah TP 1 with a value of 0.1% and the worst on Jl. Parkit TP 4 with a value of 25.2%. (3) The best throughput measurements can be found at Jl. Gajah TP 1 with a value of 93.04% and the worst on Jl. Parkit TP 4 with a value of 45.21%. Keywords: Delay, Packet loss, Throughput, TIPHON, Axence Nettols 5